Insulin Therapy Is Associated With an Increased Risk of Carotid Plaque in Type 2 Diabetes: A Real-World Study - Ke, Jiang-Feng; Wang, Jun-Wei; Zhang, Zhi-Hui; Chen, Ming-Yun; Lu, Jun-Xi; Li, Lian-Xi (Frontiers in Cardiovascular Medicine, 2021)
Background: Controversies concerning the association between insulin therapy and atherosclerotic lesions in type 2 diabetes mellitus (T2DM) remain to exist. The purpose of this study was to investigate whether insulin therapy in T2DM patients is linked with the increased risk of carotid atherosclerosis in real-world settings. Methods: We retrospectively enrolled 2,356 hospitalized patients with T2DM, including 1,716 subjects receiving insulin therapy and 640 subjects without receiving insulin therapy. Carotid atherosclerotic lesions including carotid intima-media thickness (CIMT), carotid plaque and carotid stenosis were assessed by Doppler ultrasonography and were compared between T2DM patients treated with and without insulin. Results: After adjusting for age and duration of diabetes, there was a significant increase in the prevalence of carotid plaque in both men (52.0 vs. 41.7%, p = 0.007) and women (49.6 vs. 39.7%, p = 0.003) receiving insulin therapy than in those without receiving insulin therapy. After further controlling for other confounding factors, compared with the patients without receiving insulin therapy, the risk of carotid plaque was still significantly increased not only in women treated with insulin (OR: 1.810; 95% CI: 1.155–2.837, p = 0.010), but also in men treated with insulin (OR: 1.867; 95% CI: 1.307–2.666; p = 0.001). Additionally, HOMA2-B% was higher in both women and men without receiving insulin therapy compared with those receiving insulin therapy (p < 0.001 in both men and women), but HOMA-IR was significantly higher in patients treated with insulin than in those without receiving insulin therapy (p < 0.001 in both men and women). Conclusions: Insulin therapy is associated with markedly increased risk of carotid atherosclerotic lesions in type 2 diabetes, which partly attribute to the more serious insulin resistance in T2DM patients receiving insulin therapy.